Musicology and/as social concern: imagining the relevant musicologist (Per Musi, 2015)
Social concerns and ideologies are reflected (1) in our very choice of subject or repertoire, (2) in our conscious attempts to place individua ls and repertoires in co ncrete historical or cultural context, and (3) in the paradigms and assumptions upon which we build our various arguments and narratives (progress, the 'great man,' the nation, Marxism, feminism). How might scholars of musicology act most respon sibly toward musicology students, adjunct faculty, and fellow scholars (including thos e trying new approaches)? In what non-musicological arenas might such scholars help to shape cultural and social policies? This text was originally published as Chapter 22 of: COOK, Nicholas; EVERIST, Mark (eds.). Rethinking Music. Oxford, New York: Oxford University Press, 2001. p.499-530. ISBN10: 0-19-879003-1 (hbk); ISBN10: 0-19-879004-X (pbk); ISBN13: 978-0-19-879004-4.